Life insurance convexity - Christian Kubitza; Nicolaus Grochola; Helmut Gründl (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2021)
Life insurers massively sell savings contracts with surrender options which allow policyholders to withdraw a guaranteed amount before maturity. These options move toward the money when interest rates rise. Using data on German life insurers, we estimate that a 1 percentage point increase in interest rates raises surrender rates by 17 basis points. We quantify the resulting liquidity risk in a calibrated model of surrender decisions and insurance cash flows. Simulations predict that surrender options can force insurers to sell up to 3% of their assets, depressing asset prices by 90 basis points. The effect is amplified by the duration of insurers' investments, and its impact on the term structure of interest rates depends on life insurers' investment strategy.
Keywords: G22; E52; G32; G28; 330; Life Insurance; Liquidity Risk; Interest Rates; Fire Sales; Systemic Risk